Feasibility of concervative breast surgery and intraoperative radiation therapy for early breast cancer: A single-center, open, non-randomized, prospective pilot study - CEDOLINI, CARLA (D.A. Spandidos, 2014)
Intraoperative radiotherapy (IORT) consists of an accelerated, single-dose, partial breast irradiation, performed immediately after breast conservative surgery. In the present study, we report the results of our feasibility protocol study using IORT between 2005 and 2009. We analyzed the data from a single-center, open, non-randomized, prospective pilot study including patients who underwent breast conservative surgery for invasive breast cancer between January 2005 and December 2009 at our Clinic of Surgery. Patients were divided based on IORT performance and stratified by age (≥48 or <48 years). Data were analyzed using R (version 2.15.2), considering a level of significance at P<0.05. Among the 247 eligible patients, 81 accepted the IORT protocol. Intraoperative IORT feasibility was 95.1% (77/81). In 71.4% (55/77) of the cases no postoperative complication was registered. Concerning local recurrence and overall survival, no significant difference was observed between women who underwent the IORT protocol or standard treatment. Among the patients aged <48 years, no local recurrence was noted after IORT protocol, and among women aged ≥48, local recurrences developed later in patients treated with IORT than with standard treatment. IORT represents a feasible and promising technique for the treatment of early breast cancer, with low morbidity, and beneficial aesthetic and oncologic results. Further studies are required in order to extend the inclusion criteria and offer IORT to a larger number of breast cancer patients.